Political Communication of the Indonesian People's Wave Party (Gelora) Recruitment In Medan City - DTM Muhammad Rezky Ananda; Azhar Azhar; Anang Anas Azhar (UNIVERSITAS PAKUAN, 2023)
This study seeks to investigate the political communication of the Indonesian Wave of the People Party (Gelora) in Medan City. As expected, the purpose of political recruitment is to address the human resource demands of political parties. This recruiting contributes to the fulfillment of the Election Law's standards, making Gelora an appropriate party in the future. This work use qualitative research and descriptive analysis as its methodology and methodology, respectively. The findings of this study indicate that, in order to attract members, the DPD Gelora City of Medan uses various political communications, including mass communication, marketing communication, interpersonal communication, and organizational communication, to shape its image and public opinion. Second, Gelora's member recruitment process is public and governed by established norms. The registration procedure can be completed immediately by visiting the Gelora secretariat, online via the website or application, or by registering with the internal administration of Gelora. Thirdly, Gelora's recruitment of members is bolstered by a number of elements, including the group's constant appearance of cohesion and its concern for those affected by calamity. Fourth, the recruitment of members by Gelora is hindered by a number of issues, including the disinterest of some individuals in Gelora, the tug-of-war in the recruitment of community leaders, and the lack of public interest in politics.